A standardized protocol for motion recordings of the shoulder - van der Helm, F. C. T. (1997)
The comparison and exchange of motion data is hampered by the lack of a standardized description. A standard is proposed for the description of three-dimensional motions of the shoulder. It is shown how the known 3-D motion recording methods (roentgen, palpation and video) can adapt to the proposed protocol. Three steps are involved: Determination of local co-ordinate systems using bony landmarks, use of tracking markers to measure rotations of the local co-ordinate systems and choice of reference frame and order of Euler angles for motion description.